Приключения шести лейтенантов, или о новом гипотетическом поджанре современного российского военно-исмторического фильма о Второй мировой (Великой Отечественной) войне - Kajtoch, Wojciech (Przegląd Wschodnioeuropejski, 2026)
The article identifies the emergence of a new subgenre in contemporary Russian war cinema – the “modern allegorical-symbolic tale of a lieutenant”. Its origin is traced to Jaropolk Lapshin’s 1989 film Before Dawn, in which a young NKVD officer undergoes an ideological transformation: he loses faith in Stalinism and discovers the moral heroism of the persecuted. Kajtoch argues that this work refers to the so-called “lieutenant’s prose” of the 1960s – literature portraying war through the eyes of young officers – but employs its narrative scheme for new, post-totalitarian purposes. The author discusses subsequent films – The Forty-Five, A Local Engagement, Lieutenant Suvorov, The Demoted, and Three Days of Lieutenant Kravtsov – which depict the maturation of young commanders and their confrontation with the absurdity of war. In these films, a simple didactic plot gradually acquires an allegorical dimension. In the best examples, it becomes enriched with moral and existential meanings: war turns into a space of trial, death into an experience of purification, and the protagonists’ fate into a metaphor of spiritual redemption. Kajtoch emphasizes that the recurrence of motifs, narrative structures, and character types creates a recognizable set of generic features. At the same time, the increasingly evident symbolism – religious, moral, and metaphysical – distinguishes these films from traditional realist war cinema. Thus, the new subgenre of Russian war film combines the framework of a popular action narrative with a deeper reflection on faith, the meaning of life, and human responsibility in the face of history.